2016
DOI: 10.2147/ceor.s114699
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating health-related quality of life in type 1 diabetes: a systematic literature review of utilities for adults with type 1 diabetes

Abstract: Background and aimsType 1 diabetes is a chronic condition associated with micro- and macrovascular complications that have a notable impact on health-related quality of life, the magnitude of which can be quantified via the use of utility values. The aim of this review was to conduct a systematic literature review to identify and compare published health state utility values for adults with type 1 diabetes both, with and without diabetes-related complications.MethodsLiterature searches of the PubMed, EMBASE, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 52 publications
3
34
0
2
Order By: Relevance
“…It is a chronic metabolic disorder characterized by elevated blood glucose levels due to the body's impaired insulin secretion and/or insulin resistance [1]. Persistent diabetes devastates vascular and nerve systems, causing many severe life-threatening complications (e.g., cardiovascular diseases, neuropathy, diabetic foot complications, diabetic retinopathies, or renal failure) and increasing the risk of hospitalization and mortality [2][3][4]. This disease has now been among the leading causes of disease burden worldwide [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a chronic metabolic disorder characterized by elevated blood glucose levels due to the body's impaired insulin secretion and/or insulin resistance [1]. Persistent diabetes devastates vascular and nerve systems, causing many severe life-threatening complications (e.g., cardiovascular diseases, neuropathy, diabetic foot complications, diabetic retinopathies, or renal failure) and increasing the risk of hospitalization and mortality [2][3][4]. This disease has now been among the leading causes of disease burden worldwide [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ensuring that people living with diabetes have a good quality of life (QOL) and can function adequately has become the ultimate goal of diabetic care [7]. Research increasingly looks to QOL as a favorable outcome of interventions focused on diabetes [2,6]. QOL is a multidimensional concept that does not have a unified definition [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that diabetes has a strong negative impact on HRQOL, relative to the general population (Abuawad 2013;Jain et al 2014;Nielsen et al 2016), especially in the presence of complications (Hirai et al 2013;Smith-Palmer et al 2016). Diabetic neuropathy greatly reduces the quality of life in people with DM through increased disability and assuming more hospitalizations than other diabetic complications (Mahmood et al 2009;Tesfaye and Selvarajah 2012;Abuawad 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It was considered that patients could suffer complications from five main groups: hypoglycemia, cardiovascular, neuropathy, nephropathy, and ophthalmological . Each complication was computed with increased medical costs and a utility decrement per patient of up to −0.29 . Yearly costs and quality‐of‐life scores (i.e., utility weights) associated with each state were computed.…”
Section: Methodsmentioning
confidence: 99%